ALIH WAHANA MANGA KUSURIYA NO HITORIGOTO KE DALAM ANIME - Theresia Ni Putu Tiara Supantri; I Made Budiana; Ni Putu Candra Lestari (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2025)
The title of this research is “Transformation from Kusuriya no Hitorigoto Manga into Anime”. This study aims to determine the transfer of vehicles sourced from literary works in the form of manga into anime in the form of shrinkage, addition and varied changes. The method used in this research is descriptive analysis method. This research uses the theory Transformation by Damono and Structural by Stanton. Based on the results of the study, it was found that the removed, addition and changes varied in the intrinsic elements that occurred in the vehicle transfer from manga to anime. The changes include; 1) removed parts from manga that occurs in the plot and setting; 2) addes parts from anime that occurs in the plot and setting (setting place and time); 3) varied changes in the storyline that occur due to changes in the function of the story Keywords: transformation, anime, manga